Methodological Frontier in Operational Analysis for Roundabouts: A Review - Giuffrè, Orazio; Granà, Anna; Tumminello, Maria Luisa (Frontiers in Built Environment, 2016)
Several studies and researches have shown that modern roundabouts are safe and effective as engineering countermeasures for traffic calming, and they are now widely used worldwide. The increasing use of roundabouts and, more recently, turbo and flower roundabouts, has induced a great variety of experiences in the field of intersection design, traffic safety and capacity modelling. As for unsignalized intersections which represent the starting point to extend knowledge about the operational analysis to roundabouts, the general situation in capacity estimation is still characterized by the discussion between gap acceptance models and empirical regression models. However, capacity modelling must contain both the analytical construction and then solution of the model, and the implementation of driver behavior. Thus, issues on a realistic modelling of driver behavior by the parameters that are included into the models are always of interest for practioners and analysts in transportation and road infrastructure engineering. Based on these considerations, this paper presents a literature review about the key methodological issues in the operational analysis of modern roundabouts. Focus is made on the aspects associated with the gap acceptance behavior, the derivation of the analytical-based models and the calculation of parameters included into the capacity equations, as well as steady state and non-steady state conditions and uncertainty in entry capacity estimation. At last, insights on future developments of the research in this field of investigation will be also outlined.